PENGARUH DAYA TARIK WISATA DAN AKSESIBILITAS TERHADAP MINAT WISATAWAN BERKUNJUNG KEMBALI KE DESA WISATA LEWOMADA KABUPATEN SIKKA - Anna Inang Wulohering; Magdalena Silawati Samosir; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2026)
This study aimed to: (1) describe tourists' revisit intention, tourist attraction, and accessibility; (2) analyze the effect of tourist attraction and accessibility on tourists' revisit intention, both partially and simultaneously. The population in this study consisted of tourists who visited Lewomada Tourism Village, Sikka Regency, in 2025, totaling 1,426 people. Due to the relatively large population size, the sample was determined using the Hair method, resulting in 65 respondents. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, specifically multiple linear regression. Hypothesis testing was conducted using the t-test and F-test. The results of the descriptive analysis indicated that tourists' revisit intention was in the good category, tourist attraction was also in the good category, while accessibility was in the fairly good category. The t-test results showed that, partially, tourist attractions had a positive and significant effect on tourists' revisit intention. Similarly, accessibility also had a positive and significant effect on tourists' revisit intention. The F-test results indicated that tourist attraction and accessibility simultaneously had a significant effect on tourists' revisit intention. The coefficient of determination analysis showed that both independent variables were able to explain 35.3% of the variation in tourists' revisit intention to Lewomada Tourism Village, Sikka Regency.